Foundations of entrepreneurial strategy. (21st February 2019) - Gans, Joshua S.; Stern, Scott; Wu, Jane
Abstract : Research Summary: This paper develops an integrated framework linking the nature of the entrepreneurial choice process to the foundations of entrepreneurial strategy. Because entrepreneurs face many alternatives that cannot be pursued at once, entrepreneurs must adopt (implicitly or explicitly) a process for choosing among entrepreneurial strategies. The interplay between uncertainty and learning has the consequence that commitment‐free analysis yields multiple, equally viable alternatives from which one must be chosen. This endogenous gap between optimization and choice is a central paradox confronting entrepreneurs. Resolving this allows for a reformulation of the foundations of entrepreneurial strategy, emphasizing the role of choice rather than the centrality of the strategic environment. Managerial Summary: The central strategic challenge for an entrepreneur is how to choose: entrepreneurs often face multiple potential strategies for commercializing their idea but due to the constraint of limited resources, cannot pursue them all at once. At the same time, entrepreneurs are venturing into new domains and as such, must choose under conditions of high uncertainty with only noisy learning available. This paper explores the interplay between these unique conditions that shape the entrepreneurial choice process, finding that often, the process will not yield a single best strategy but instead several equally attractive strategic alternatives. A key implication is that entrepreneurs cannot simply choose what not to do, but instead must proactively decide which equally viable alternatives to leave behind when choosing an entrepreneurial strategy.